2020
DOI: 10.11604/pamj.2020.36.320.19814
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial distribution of severe paediatric intussusception in KwaZulu-Natal province, South Africa

Abstract: Introduction intussusception in South African (SA) children is often severe. A proportion of cases require management at quaternary hospitals which are a scare resource in SA. A geospatial investigation of severe paediatric intussusception (SPI) in the KwaZulu-Natal (KZN) province of SA would assist with identifying regions which should be targeted for preventative interventions. This could reduce resource utilisation for this condition at quaternary hospitals. The objective of this study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(61 citation statements)
references
References 17 publications
0
61
0
Order By: Relevance
“…The spatial aspects of the intussusception cases, including their geographical distribution, distance, density and direction, are presented in this manuscript. Previous studies have reported that the epidemiology of intussusception varies according to the country and region 2 , 26 . However, granular examination of the location of patients reported at sentinel surveillance network hospitals, with the help of geostatistics techniques, revealed that the regional pattern inferred from hospital-based studies may be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial aspects of the intussusception cases, including their geographical distribution, distance, density and direction, are presented in this manuscript. Previous studies have reported that the epidemiology of intussusception varies according to the country and region 2 , 26 . However, granular examination of the location of patients reported at sentinel surveillance network hospitals, with the help of geostatistics techniques, revealed that the regional pattern inferred from hospital-based studies may be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…The eThekwini district is densely populated (3,702,231) comprising of urban, semi-urban, and rural areas [ 24 ]. We selected study clinics from the three settings; (i) 2 facilities (Ithembalabantu and D clinic) in a densely populated Umlazi township also known to have high HIV prevalence of 35%, [ 25 ] (ii) Pinetown clinic in Pinetown, a semi suburb town (these are places that offer a balance between township and suburb tranquillity) surrounded by townships and informal settlements who all seek services at the facility and (iii) Qadi clinic in rural Umzinyathi district municipality north of eThekwini municipality. UMzinyathi district has high levels of poverty, unemployment, and HIV/AIDS [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…This was one of my intentions with writing and directing Devi (2019), with the hope that such an accessible text and production could reach and evoke in audiences a deep-rooted response to my work, especially my fellow ISAW, SAIW and/or SAWOID. As outlined above, my thesis consists of nine chapters, each with a particular focus.…”
Section: 7: Autoethnographic Reflexivitymentioning
confidence: 99%
“…My identity as an SAIW has driven every aspect of my work, and is the heart of my study. Uncovering how this influenced the play, Devi (2019), I wrote and staged, as well as the research I conducted, is thus hugely significant to my thesis.…”
Section: 7: Autoethnographic Reflexivitymentioning
confidence: 99%
See 1 more Smart Citation